Financial Inclusion Strategies and Its Role in Achieving Sustainable Development: A Comparative Study Between Selected Countries of the European Union (Eurasian Journal of Media and Communications, 2025)
This research aims to analyze the role of financial inclusion strategies in supporting the achievement of sustainable development (SD) goals, through a comparative applied study between four selected countries of the European Union: Germany, France, Spain, Sweden, and Denmark. The study relied on a comparative analytical approach, based on data issued by international organizations and official financial institutions, such as the World Bank and the European Commission, to assess the level of financial inclusion and the extent to which it reflects on SD indicators in their economic, social and environmental dimensions. The results of the study showed a positive correlation between higher levels of financial inclusion and improved indicators of SD, especially in countries with advanced inclusive policies such as Sweden and Germany, while countries such as Romania continue to face challenges in equitable access to financial services, which limits the achievement of balanced development. The adoption of finch and policies targeting vulnerable groups has also been shown to play an important role in reducing gaps and promoting social and economic inclusion. The research recommends the need to strengthen cooperation between European countries to exchange experiences and adopt more comprehensive policies linking financial plans with environmental and social strategies, to ensure the achievement of the SD Goals by 2030.